From Carbon Footprints to Competitive Edges: Analyzing Environmental Efficiency in Aviation - Zehra Vildan Serin; Oya Öztürk (Verimlilik Dergisi)
Purpose: This study conducts a comprehensive analysis of environmental efficiency in the aviation industry, focusing on 19 global airline companies employing diverse business models.Methodology: Utilizing Data Envelopment Analysis for 2017 to 2022, the research quantifies efficiency levels based on input and output variables, including Fuel Consumption, Revenue Passenger Kilometers, Greenhouse Gas Emissions, and Total Income.Findings: Noteworthy findings reveal that Alaska Airlines (VRS=1), Lufthansa (VRS=1), Spirit Airlines (VRS=1), and Delta Air Lines (VRS=1) consistently operated at the environmental efficiency frontier, showcasing a proportional relationship between input and output values.Originality: The dynamic nature of the aviation industry, coupled with the economic implications of environmental initiatives, necessitates a nuanced understanding of airlines' sustainability efforts. Policymakers are urged to consider measures such as the effective introduction of Sustainable Aviation Fuels and large-scale strategies to reduce aviation-related greenhouse gas emissions.